(untitled) (Fiep Bulletin - online, 2014)
The study has been a part of project VE GA 1/0759/12. The aim of the study was to widen and to inn Faculty of Physical Education and Sport ovate current knowledge about the opinions of the boys and girls of chosen high schools in Bratislava on the conditions of educational process and physical activity in physical and sport education classes in relation to the differentiated level of spatial and material conditions. Chosen high schools were divided into two groups (schools with higher and lower level of spatial and material conditions) on the basis of analysed current state of the spatial and material conditions of physical and sport education teaching process. There were significant differences between the boys of two groups of schools. Boys attending the schools with higher level of spatial and material conditions were more active and more motivated than the boys attending the schools with lower level of spatial and material conditions. There were no significant differences in activity and motivation of girls of the two groups of schools. On the other hand, there were significant differences between the girls of the two groups of schools concerning the participation in classes. Girls attending the schools with the higher level of spatial and material conditions participated more in comparison with the girls attending schools with lower level of spatial and material conditions. There were no significant differences between the boys. Acknowledgment: The study is a part of project VE GA 1/0759/12.